GRAPHIC-ANALYTICAL DETERMINATION OF THE DEPENDENCE OF THE GEAR RATIO OF ROAD TRAINS IN CURVILINEAR MOTION - Alexey Amosov, Vladislav Golikov, Ekaterina Mikhailova, Oleg Rozhdestvensky (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Providing the possibility of unification of the trajectory of movement with the existing infrastructure is a technical problem, the solution of which can be largely facilitated with the existence of sufficiently accurate productive methods of structural-parametric analysis of the geometry of curvilinear movement as a whole. Therefore, the team of authors decided to identify a methodological basis for determining the dependence of the gear ratio of two and three-link road trains. This will simplify calculations in the future, receive comprehensive and practical recommendations on the design of the wheel drive and the number of links of the road train.